Social and Economic Implications of HIV/AIDS: Evidence from West Bengal. - Sarker, Debnarayan (2011)
Based on household level’ field survey in West Bengal State in Indian context, this study suggests that poverty and lower level of human capital provide the basic initiatives for both rural –urban migration and risky occupational choice for household’s income, and thus contributes to the spread of HIV/AIDS. Also, the HIV/AIDS epidemic of those economically and socially disadvantaged households leads to the consequence of absolute economic and social poverty within a short period after its detection. Despite such a consequence of absolute economic and social poverty, the benefit of actions by government or non-government organizations is insignificant for them.